A self-powered multi-broadcasting wireless sensing system realized with an all-in-one triboelectric nanogenerator. (August 2019) - Khan, Asif Abdullah; Mahmud, Alam; Zhang, Steven; Islam, Shariful; Voss, Peter; Ban, Dayan
Abstract: The ubiquitous sensors at the core network of Internet of Things (IoT) have accelerated the realization of micro/nano systems that necessitate not only the development of self-powered sensors but also requires a reliable wireless communication mode. Here, a self-powered multi-broadcasting wireless sensing system based on an all-in-one triboelectric nanogenerator (TENG) is reported, which can simultaneously power up a custom-made wireless node and act as a sensor. The whole device and the system are encapsulated in a unique compact structure, in which the top segment consists of a spring-assisted multifunctional TENG (MTENG) and, the bottom section contains an integrated energy management and Bluetooth transmitter module. Following the structural and material modifications, the top unit of the MTENG is used to detect vibration frequency and amplitude by correlation with the TENG output voltage. The device has been employed to successfully detect the running frequency of a linear shaker and various generated signals. Owing to the nanostructured material surfaces, the device yields an output current of 300 μA and a power density of 4 W/m 2 with the normal hand pressing. Moreover, the developed portable MTENG is also assessed to remotely monitor automobile engine vibration and is expected to result in a myriad of applications. Graphical abstract: Image 1 Highlights: A novel all-in-one triboelectric nanogenerator enabling multi-broadcasting wireless monitoring system. Integration of organic/inorganic nanostructured materials leads to higher energy conversion efficiency and reliable wireless monitoring. The unique compact and portable device design incorporate an optimized TENG sensor and TENG harvester together with integrated energy management, storage and RF transmission module to detect vibration characteristics in a wide range of frequencies. A very promising nanogenerator in designing a self-powered structural health monitoring system in an automobile engine, jet engine, etc. due to mechanical robustness, high output, repeatability, and long-term reliability.